Comprehensive reconstruction and in silico analysis of Aspergillus niger genome‐scale metabolic network model that accounts for 1210 ORFs. Issue 3 (17th October 2016) - Lu, Hongzhong; Cao, Weiqiang; Ouyang, Liming; Xia, Jianye; Huang, Mingzhi; Chu, Ju; Zhuang, Yingping; Zhang, Siliang; Noorman, Henk
ABSTRACT: Aspergillus niger is one of the most important cell factories for industrial enzymes and organic acids production. A comprehensive genome‐scale metabolic network model (GSMM) with high quality is crucial for efficient strain improvement and process optimization. The lack of accurate reaction equations and gene‐protein‐reaction associations (GPRs) in the current best model of A. niger named GSMM iMA871, however, limits its application scope. To overcome these limitations, we updated the A. niger GSMM by combining the latest genome annotation and literature mining technology. Compared with iMA871, the number of reactions in iHL1210 was increased from 1, 380 to 1, 764, and the number of unique ORFs from 871 to 1, 210. With the aid of our transcriptomics analysis, the existence of 63% ORFs and 68% reactions in iHL1210 can be verified when glucose was used as the only carbon source. Physiological data from chemostat cultivations, 13 C‐labeled and molecular experiments from the published literature were further used to check the performance of iHL1210. The average correlation coefficients between the predicted fluxes and estimated fluxes from 13 C‐labeling data were sufficiently high (above 0.89) and the prediction of cell growth on most of the reported carbon and nitrogen sources was consistent. Using the updated genome‐scale model, we evaluated gene essentiality on synthetic and yeast extract medium, as well as the effects of NADPH supply on glucoamylase production in A. niger . In summary, the new A. niger GSMM iHL1210 contains significant improvements with respect to the metabolic coverage and prediction performance, which paves the way for systematic metabolic engineering of A. niger . Biotechnol. Bioeng. 2017;114: 685–695. © 2016 Wiley Periodicals, Inc. Abstract : Based on the latest genome annotations, the A. niger genome‐scale metabolic network model was systematically reconstructed. The new model iHL1210 contains 1, 764 reactions and 1, 210 unique ORFs. The existence of most reactions could be verified by latest RNA‐seq. The average correlation coefficients between the predicted fluxes and estimated fluxes from 13 C‐labeling data were sufficiently high. The new A. niger GSMM was obviously improved in metabolic coverage and prediction performance, which paves the way for systematic metabolic engineering of A. niger .